Responsible contracting: an approach aimed at improving social and labour practices in the property services sector - Bibby, Andrew (Geneva, 2011)
"This paper focuses on the property services sector, and in particular on the provision of cleaning and security services. Buildings need cleaning, and buildings and property also need protecting. There is a long history of companies employing cleaners, caretakers and security staff at their workplaces and premises, sometimes as direct employees but also sometimes through other – more informal – arrangements. The past 30 years or so have seen a shift away from these more traditional arrangements, however, towards more systematic approaches. The idea that companies should concentrate on their core business activities and use contractors or outside suppliers for those which are peripheral is now deeply embedded in business practice and it has resulted among other things in the rapid growth in recent years of companies which make it their business to specialize in property and facilities services. "